KEANEKARAGAMAN JENIS ROTAN DI KAWASAN TAMAN NASIONAL LORE LINDU DESA WUASA KECAMATAN LORE UTARA KABUPATEN POSO - Ardyanto Peluru; Adam Malik; I Nengah Korja (ForestSains, 2019)
Rattan is a nontimber forest products that can contribute to society in improving household income. Rattan is a climbing plant in the family of Palmae. Rattan grows wild in the forest, and there is also planted by the community. Forest in Indonesia has a high diversity of rattan species, which are about 312 species of rattan growing in the forests of Indonesia. Of the total 13 genera of rattan in the world, 8 genera of which grow in Indonesia. The aim of research to determine the diversity of rattan species in the study site.  This research was conducted for three months, from November 2015 - January 2016 in Lore Lindu National Park area.  This research applied a survey method through using a subjective observation plot (purposive sampling).  This research put on 3 line transects with a length of 1.000 m. the distance between the transect was 100 m. Observation was carried out following the transect line and in the area which found rattan made a plot size of 20 m X 20 m. The number of plots used in this study was 20 plots. The result showed that the number of rattan species in the study site were 7 species of rattan consisting of 57 groves and 214 individuals consisting of 48 individuals of rotan batang (Calamus zollingeri Becc) , 41 individuals of  rotan buku dalam (Calamus shymphysipus Becc), 31 individuals of rotan tumanu (Calamus ornatus var.celebicus Becc), 21 individuals of rotan ibo (Calamus ahliduri Becc), 22 individuals of rotan karuku (Calamus Macrosphaerica Becc), 25 individuals of rotan pai (Calamus coordersianus Becc), and 16 individuals of rotan botol (Daemonorop robusta Warb).